Review of Hydrological Peculiarities of the Flooding in the Amur Region with the Purpose to Establish a Complex of Sanitary-Anti-Epidemic Actions for Minimization of Social Implications - O. P. Kurganova; E. N. Yavkina; G. V. Sitnikova (Проблемы особо опасных инфекций, 2014)
Described are the chronology and main peculiarities of floods in the Amur Region within the historical period since 1872 till present time. Given are the data on the damage to the Amur-river territory economy as a result of catastrophic high waters in 1928, 1950s, 1984, 2007. Comprehensively discussed are the peculiarities of the flooding, August-September 2013 as one of the most intense and prolonged in the history of the hydro-meteorological observations in the Far East. It is found out that Zeisk and Bureisk hydroelectric power stations turned out to be the only buffer storage restraining two thirds of the water volume of Zeya and Bureya rivers inflow in their flowages over a period of flood. Outlined are the general guidelines for emergency response activities under high water conditions for the Rospotrebnadzor Administration Quarters in the Amur Region. Implementation of the complex of actions through the offices of the territorial Rospotrebnadzor institutions in cooperation with the executive authorities has allowed for the prevention of epidemiological implications, providing for favorable sanitary-epidemiologic situation at the time of high water.